Urban Agriculture Practices and Households’ Livelihoods in Ondo State, Nigeria - Akinnagbe, Oluwole Matthew; Ipinmoye, Obadamilola Enitan (Journal of Agricultural Extension, 2022)
The study examined the effects of urban agriculture on households’ livelihoods in Ondo State, Nigeria. A multistage sampling procedure was employed in selecting 150 respondents. Data were obtained through the use of interview schedule and analysed using percentage, charts, and mean statistic. Results revealed that the major crop and livestock kept were leafy vegetables (100.0%) and broilers chicken (57.0%), respectively. The majority (82.0%) of the respondents that practised urban agriculture had no contact with extension agent. The practice of urban agriculture had significant effects on respondents’ livelihood in term of improvement in standard of living from 85.0% to 98.0%, and improvement in saving pattern from 66.7% to 100.0%. The practice of urban agriculture had also led to an improved knowledge of the respondents. The extension services of Ondo State Agricultural Development Programme should be extended to those practicing urban agriculture. This will go a long way in improving and sustaining households’ livelihoods.